Drug–induced gingival overgrowth after cyclosporin A therapy - Ambicki, Miłosz; Brodowski, Robert; Mucha, Marta; Migut, Małgorzata; Malawski-Róg, Adam; Stopyra, Wojciech; Lewandowski, Bogumił (European Journal of Clinical and Experimental Medicine, 2017)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Drug–induced gingival overgrowth is a condition caused by side effects of treatment with one of three types of drugs: phenytoin (used in epilepsy treatment), cyclosporin A (used in transplantology after allogeneic organ transplants) and calcium channel blockers (in the treatment of hypertension). Gingival overgrowth leads to the development of inflammation within the gums and periodontium, reduced comfort in a patient’s life, and consequently even loss of teeth. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of this study was to present the issue of drug–induced gingival overgrowth based on a review of the literature and observations of patients treated in the Clinical Department of Maxillo-Facial Surgery, Frederic Chopin Provincial Specialist Hospital in Rzeszów. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Case description. Massive gingival overgrowth requires surgical management. Attention should be paid to multidisciplinary cooperation in case of patients qualified for a transplant. It is also important to qualify and evaluate the state of the oral cavity prior to the implementation of immunosuppressive medication, instruction of patients on oral hygiene and removal of the outbreaks of infection.